Assessment of the Minimum Clinically Important Difference in the Smartphone-based 6-minute Walking Test After Surgery for Lumbar Degenerative Disc Disease. Issue 18 (15th September 2021) - Zeitlberger, Anna M.; Sosnova, Marketa; Ziga, Michal; Regli, Luca; Bozinov, Oliver; Weyerbrock, Astrid; Stienen, Martin N.; Maldaner, Nicolai
Abstract : Study Design: Prospective cohort study. Objective: The aim of this study was to determine the minimum clinically important difference (MCID) of the 6-minute walking test (6WT) after surgery for lumbar degenerative disc disease (DDD). Summary of Background Data: The smartphone-based 6WT is a valid and reliable tool to quantify objective functional impairment in patients with lumbar DDD. To date, the MCID of the 6WT has not been described in patients with DDD. Methods: We assessed patients pre- and 6-weeks postoperatively, analyzing both raw 6-minute walking distances (6WD; in meters) and standardized 6WT z scores. Three methods were applied to compute MCID values using established patient-reported outcomes measures (PROMs) as anchors (VAS back/leg pain, Zurich Claudication Questionnaire [ZCQ], Core Outcome Measures Index [COMI]): average change, minimum detectable change, and the change difference approach. Result: We studied 49 patients (59% male) with a mean age of 55.5 ± 15.8 years. The computation methods revealed MCID values ranging from 81 m ( z score of 0.9) based on the VAS back pain to 99 m ( z score of 1.0) based on the ZCQ physical function scale. The average MCID of the 6WT was 92 m ( z score of 1.0). Based on the average MCID of raw 6WD values or standardized z scores, 53% or 49% of patients classified as 6-week responders to surgery for lumbar DDD, respectively. Conclusion: The MCID for the 6WT in lumbar DDD patients is variable, depending on the calculation technique. We propose a MCID of 92m ( z score of 1.0), based on the average of all three methods. Using a z score as MCID allows for the standardization of clinically meaningful change and attenuates age- and sex-related differences. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the textIn this study, the minimal clinically important difference (MCID) of the 6-minute walking test was determined for the 6-minute walking distance and z scores in patients with lumbar degenerative disc disease. We propose an MCID of 92 m, corresponding to a z score of 1.0, for this patient group.